Neuromielite óptica: estudo retrospectivo das características clínicas, radiológicas e análise do tratamento dos pacientes acompanhados no Setor de Neuroimunologia, Disciplina de Neurologia, da Universidade Federal de São Paulo – Escola Paulista de Medicina - Bichuetti, Denis Bernardi [UNIFESP] (2010)
Introduction: Neuromyelitis optica (NMO) is an inflammatory, autoimmune, demyelinating disease of the central nervous system associated to antibodies targeted at the aquaporin-4. It is characterized by episodes of acute bilateral optic neuritis and myelitis, and presents as a relapsing-remitting disease in 85% of the cases. Objectives: To describe the demographic, clinical, radiological characteristics, the relation of brain abnormalities to clinical prognosis and response to immunossupressive treatment of patients with NMO followed at the Universidade Federal de São Paulo (UNIFESP). Methods: Retrospective analysis of patients followed for NMO at UNIFESP from February 1994 to July 2007. All patients fulfilled the 1999 and/or 2006 diagnostic criteria for NMO and were followed for more than six months. A subgroup of patients was selected for a study of the normal appearing white matter (NAWM) by magnetic resonance spectroscopy (MRS). Results: Forty-one patients fulfilled the inclusion criteria and were selected for analysis. Mean age of onset was 32.6 years, 69% were female and the mean follow-up for the whole cohort was 52 months. Mean annualized relapse rate observed was 1.0 relapse/year and mean progression index was 0.9 EDSS points/year. Thirty-nine percent of the patients reached EDSS 6 and the only feature associated to this outcome was incomplete recovery from first relapses. Fifty-nine percent of the patients presented with brain MRI abnormalities, but this was not associated to a worse outcome. Study of the NAWM by MRS did not disclose hidden abnormalities. Azathioprine solely or in association to prednisone was able to reduce relapses frequency and halt disability progression in 76% of the cases. Conclusions: In this series, incomplete recovery from first relapses was the only feature associated to a worse prognosis and brain abnormalities seen on MRI did not correlate to disease severity. Azathioprine was able to control disease progression in 76